Language change in the wake of empire: Syriac in its Greco-Roman context - Butts, Aaron Michael (Linguistic studies in Ancient West Semitic, 2016)
"Although it is widely acknowledged that Syriac was influenced by Greek, the specific contours of this interaction remain unclear. This study aims to present a new analysis of contact-induced changes in Syriac due to Greek. More specifically, the study intends to show that Syriac is the outcome of a particular socio-linguistic situation in which inherited Aramaic material was augmented and adapted through contact with Greek. To demonstrate this, Butts examines the place of Greek loanwords in Syriac as well as the way that Syriac-speakers replicated inherited Aramaic material on Greek, the latter being considered "grammatical replication." "--